Evaluation of a hepatitis C virus core antigen assay from venepuncture and dried blood spot collected samples: A cohort study. Issue 12 (18th September 2019) - Catlett, Beth; Lamoury, Francois M. J.; Bajis, Sahar; Hajarizadeh, Behzad; Martinez, Danica; Mowat, Yasmin; Cunningham, Philip H.; Jacka, Brendan P.; Cloherty, Gavin A; Marks, Philippa; Dore, Gregory J.; Grebely, Jason; et al.
Abstract: The global scale‐up of hepatitis C virus (HCV) diagnosis requires simplified and affordable HCV diagnostic pathways. This study evaluated the sensitivity and specificity of the HCV Architect core antigen (HCVcAg) assay for detection of active HCV infection in plasma and capillary whole blood dried blood spots (DBS) compared with HCV RNA testing in plasma (Abbott RealTime HCV Viral Load). Samples were collected from participants in an observational cohort enrolled at three sites in Australia (two‐drug treatment and alcohol clinics and one homelessness service). Of 205 participants, 200 had results across all samples and assay types and 186 were included in this analysis (14 participants receiving HCV therapy were excluded). HCV RNA was detected in 29% of participants ([95% CI: 22.6‐36.1], 54 of 186). The sensitivity of HCVcAg for detection of active HCV infection in plasma was 98.1% (95% CI: 90‐100) and 100% (95% CI: 93‐100) when compared to HCV RNA thresholds of ≥12 and ≥1000 IU/mL, respectively. The sensitivity of the HCVcAg assay for detection of active HCV infection in DBS was 90.7% (95% CI: 80‐97) and 92.5% (95% CI: 82‐98) when compared to HCV RNA thresholds of ≥12 and ≥1000 IU/mL, respectively. The specificity of HCV core antigen for detection of active infection was 100% (95% CI: 97‐100) for all samples and RNA thresholds. These data indicate that the detection of HCVcAg is a useful tool for determining active HCV infection; to facilitate enhanced testing, linkage to care and treatment particularly when testing plasma samples are collected by venepuncture.